Effectiveness of roundhouse kick in elite Taekwondo athletes - Sutima Thibordee (2018)
The roundhouse kick is a powerful attack in Taekwondo. Most athletes intently perform this kick for scoring in competition. Therefore, kinematic and kinetic analyzes of this kick were the topics of interest; however, they were separately investigated and rarely recorded for impact force. Our objectives were to investigate knee and ankle joint kinematics and electromyographic (EMG) activity of leg muscle and compare them between high-impact (HI) and low-impact (LO) kicks. Sixteen male black-belt Taekwondo athletes performed five roundhouse kicks at their maximal effort. Electrogoniometer sensors measured angular motions of ankle and knee joints. Surface EMG activities were recorded for tibialis anterior, gastrocnemius medialis, rectus femoris, and biceps femoris muscles. Based on maximal impact forces, the athletes were classified into HI and LO groups. All athletes in both groups showed greater activation of rectus femoris than other muscles. The HI group only showed significantly less plantarflexion angles than the LO group during preimpact and impact phases (P < . 0.05). During the impact phase, the HI group demonstrated significantly greater biceps femoris activation than the LO group (P < . 0.05). In conclusion, rectus femoris activation could predominantly contribute to the powerful roundhouse kicks. Moreover, high biceps femoris co-activation and optimal angle of ankle plantarflexion of about 35° could help achieve the high impact force. © 2014 Elsevier Ltd.